2006
DOI: 10.1096/fj.05-5354com
|View full text |Cite
|
Sign up to set email alerts
|

Calpain‐2 regulation of VEGF‐mediated angiogenesis

Abstract: Angiogenesis is a complex process involving endothelial cell migration, proliferation, and differentiation as well as tube formation. These processes are stimulated by a variety of growth factors such as vascular endothelial growth factor (VEGF). VEGF-induced cytoskeletal reorganization plays a crucial role in the angiogenic processes. In the present study, we evaluated the role of calpain in VEGF-induced angiogenesis in vitro and in vivo. Human pulmonary microvascular endothelial cells (PMEC) were incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 42 publications
(56 reference statements)
6
73
1
Order By: Relevance
“…We and others have previously shown evidences of a VEGF/ VEGFR2/calpain/PI3K/AMPK/Akt/eNOS/NO signaling pathway (1)(2)(3)(4). In this study, we set out to investigate any calpain dependent feedback regulation of VEGFR2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have previously shown evidences of a VEGF/ VEGFR2/calpain/PI3K/AMPK/Akt/eNOS/NO signaling pathway (1)(2)(3)(4). In this study, we set out to investigate any calpain dependent feedback regulation of VEGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that calpain activity is increased within 10 min of VEGF stimulation of endothelial cells, which can be inhibited by antagonist of the VEGF receptor (1)(2)(3)(4). In addition, we have demonstrated an important role of calpain in mediating VEGFinduced PI3K/AMPK/Akt activation and consequent eNOS phosphorylation and nitric oxide (NO) production (1).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 91%
See 1 more Smart Citation
“…Expression of calpain-1 and calpain-2 was silenced using siRNA technology (73). The target sequences for the mRNA of calpain-1 and calpain-2 were 5′-AAGCTAGTGTTCGTG-CACTCT-3′ and 5′-AAACCAGAGCTTCCAGGAAAA-3′, respectively.…”
Section: Figure 15mentioning
confidence: 99%
“…1 Their most studied involvement is in the regulation of the dynamic rearrangements of cytoskeletal architecture during cell migration 2 : depending on the cellular context, a range of stemming effects have been shown to be controlled by calpains such as synaptic function/remodelling in neurons 3 or angiogenesis in endothelial cells. 4 m-calpain and m-calpain, encoded by Capn1 and Capn2, respectively, are ubiquitously expressed and require a common 28-kDa regulatory subunit encoded by the Capns1 gene for stability and activity. Targeted disruption of Capns1 is embryonic lethal at day 10-11, due to severe defects in vascular development.…”
Section: Introductionmentioning
confidence: 99%